On becoming good women: a study on 'the fragmented self' in Malaysian Muslim women's writing in English - Abdul Manaf, Nor Faridah (Korean Society for Feminist Studies in English Literature, 2007)
Malaysian Muslim women’s writing in English is a new literary phenomenon, and hence, there is not much critical literature. This paper examines some samples of writings in English by Malaysian Muslim women. It begins by providing the background of English language and literature in Malaysia in an attempt to address the complexities of writing in English in Malaysia. The paper also raises issues of importance to Malaysian Muslim women writers by focusing on the struggles and conflicts that they encounter, writing as Muslim women. This is because of cultural tensions faced as a result of urbanization and modernization, which bring in new values, very often based on Western mores. The paper examines how identities are fragmented as these women address taboo subjects like sex, sexuality, and illegal abortions. Their writings express the tension between succumbing to the dictates of society and the need to expose reality as it is. Muslim women writers are also at pains to voice their Muslim identity in a world so misinformed on matters relating to Islam and Muslim women. Muslims are expected to be virtuous by their religion, and where the women are concerned, the expectations are often higher than for men as interpretations of “good” behavior are often focused on women. This unbalanced representation of Muslim women, be it by Muslims themselves or Western media, has elicited gross misrepresentations of women in Islam or Muslim women in general. This paper documents the voices of Malaysian Muslim women writers in their attempts to represent themselves and their world but not without conflicts and predicaments. The paper focuses on the women’s ‘fragmented selves’ as they struggle to define and redefine what it is like to have multiple roles as Muslim women.